If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35(2x + -1) = 4(x + -4) + 3x Reorder the terms: 35(-1 + 2x) = 4(x + -4) + 3x (-1 * 35 + 2x * 35) = 4(x + -4) + 3x (-35 + 70x) = 4(x + -4) + 3x Reorder the terms: -35 + 70x = 4(-4 + x) + 3x -35 + 70x = (-4 * 4 + x * 4) + 3x -35 + 70x = (-16 + 4x) + 3x Combine like terms: 4x + 3x = 7x -35 + 70x = -16 + 7x Solving -35 + 70x = -16 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -35 + 70x + -7x = -16 + 7x + -7x Combine like terms: 70x + -7x = 63x -35 + 63x = -16 + 7x + -7x Combine like terms: 7x + -7x = 0 -35 + 63x = -16 + 0 -35 + 63x = -16 Add '35' to each side of the equation. -35 + 35 + 63x = -16 + 35 Combine like terms: -35 + 35 = 0 0 + 63x = -16 + 35 63x = -16 + 35 Combine like terms: -16 + 35 = 19 63x = 19 Divide each side by '63'. x = 0.3015873016 Simplifying x = 0.3015873016
| 8x+y-5=0 | | 5x+6+9x+5= | | 18-3v=42 | | 12x+b=180 | | 10x+5x-20=25 | | 2x+(5*5)=25 | | -5(-4m-8)=-2m-26 | | 78y+45=13 | | (2x+24)+(4x+36)=180 | | -w-7=-74 | | -28+y=-3 | | f(x)=x^2-64 | | 5X-(3X-2)=28 | | logx(2)=96 | | 4x^4-x^3-36x^2-111x+30=0 | | 3x+4=x+23 | | 100+9x=210+6x | | 3(y-2)=2(y+5) | | f(5)=3x^2-6x+4 | | 27x+13y+91z=667 | | 27x+6y=17 | | 135+23x=1+45x | | y-12=2 | | 4(-3v-1)-4=88 | | -6-5y=13 | | 35y+7=17 | | (2x+1)(x-5)=2x^2-1 | | xn=3n+11 | | 7(7b-3)=-413 | | (z-4)(z-10)=0 | | 7(x^2+1)=50x | | 36+4p=-4-3(p-4) |